2014
DOI: 10.3389/fpsyg.2014.00943
|View full text |Cite
|
Sign up to set email alerts
|

A method for generating an illusion of backwards time travel using immersive virtual reality—an exploratory study

Abstract: We introduce a new method, based on immersive virtual reality (IVR), to give people the illusion of having traveled backwards through time to relive a sequence of events in which they can intervene and change history. The participant had played an important part in events with a tragic outcome—deaths of strangers—by having to choose between saving 5 people or 1. We consider whether the ability to go back through time, and intervene, to possibly avoid all deaths, has an impact on how the participant views such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 30 publications
3
41
0
Order By: Relevance
“…However, researchers have demonstrated that immersive VR systems can be used to create body ownership illusions, in which "healthy subjects experience an artificial body as if it were their own physical body" (Maselli and Slater, 2013). In other words, users may unconsciously accept an avatar representation of themselves as their own body and respond to events involving their avatar, such as possible harm (González-Franco et al, 2014), uncontrolled movements (Pomes and Slater, 2013), expected social behaviors (Kilteni et al, 2013), and even time travel (Friedman et al, 2014). If immersive technologies can be used to induce such body ownership illusions, particularly time travel, they can clearly be used to place the audience within a news story.…”
Section: Body Ownershipmentioning
confidence: 99%
“…However, researchers have demonstrated that immersive VR systems can be used to create body ownership illusions, in which "healthy subjects experience an artificial body as if it were their own physical body" (Maselli and Slater, 2013). In other words, users may unconsciously accept an avatar representation of themselves as their own body and respond to events involving their avatar, such as possible harm (González-Franco et al, 2014), uncontrolled movements (Pomes and Slater, 2013), expected social behaviors (Kilteni et al, 2013), and even time travel (Friedman et al, 2014). If immersive technologies can be used to induce such body ownership illusions, particularly time travel, they can clearly be used to place the audience within a news story.…”
Section: Body Ownershipmentioning
confidence: 99%
“…78,79 A more sophisticated version of this setup was repeated in an HMD-based study (Friedman et al, 2014) concerned with embodiment and time travel, where realistic virtual characters were portrayed. In terms of responses to the dilemma they were similar to the other studies.…”
Section: Virtual Representations Of Moral Dilemmasmentioning
confidence: 99%
“…For example, Friedman et al (Front Psychol 2014; 5:943) described a method based on immersive VR for generating an illusion of having traveled backward through time to relive a sequence of events in which the individual can intervene and change history. 3 The authors consider this question: what if someone could travel back through time to experience a sequence of events and be able to intervene in order to change history? To answer this question, Friedman et al simulated a sequence of events with a tragic outcome (deaths of strangers) in which the participant can virtually travel back to the past and undo actions that originally led to the unfortunate outcome.…”
Section: In the Spotlightmentioning
confidence: 99%